Rescue of male infertility by human PRSS55 in transgenic mice establishes a contraceptive research model - Courtney M. Sutton; Kohei Umezu; Daisuke Mashiko; Masahito Ikawa; Irina V. Larina; Thomas X. Garcia; Martin M. Matzuk (Scientific Reports)
Abstract The development of non-hormonal male contraceptives requires validated preclinical models. This study investigated whether human orthologs of two mouse testis-specific serine proteases, PRSS55 and TMPRSS12, both essential for male fertility in mice, could functionally rescue the infertility phenotypes of their respective knockout mouse lines. We generated transgenic mouse lines expressing human PRSS55 with either an extracellularly or intracellularly positioned C-terminal 3xFLAG tag (RES GPI or RES TM), and a line expressing human TMPRSS12 with a C-terminal 3xFLAG tag (T12 RES), all on their respective mouse null backgrounds. Fertility was assessed through continuous mating trials, and sperm parameters were evaluated. Both hPRSS55 rescue lines sired offspring; RES GPI males exhibited partially restored fertility with significantly fewer pups per litter compared to controls, while RES TM males demonstrated fertility comparable to controls. In contrast, T12 RES males remained infertile, exhibiting severe defects in sperm motility and other parameters, despite confirmed transgene mRNA expression. These findings indicate that human PRSS55, particularly when tagged intracellularly, can functionally replace its mouse counterpart, validating the RES TM line as a promising model for testing human PRSS55-targeted contraceptives. The inability of hTMPRSS12 to rescue fertility highlights challenges potentially due to sequence divergence or unconfirmed protein expression levels.